A review on solid dispersion: a modern formulation approach in drug delivery system - Gupta, Dheeraj Kumar; Negi, Ritu; Kala, Shivani; Juyal, Divya; Rawat, Geeta (Journal of Applied Pharmaceutical Research, 2014)
Drugs those are given as solid dosage form and having low solubility often have a lack of flexibility in drug formulation and administration. The dissolution rate could be the rate-limiting process in the absorption of a drug from a solid dosage form of relatively insoluble drugs. Solid dispersion technologies are promising techniques for improving the water solubility, and hence dissolution and bioavailability of hydrophobic drugs. It is done for Biopharmaceutical Classification System (BCS) II Class drugs. Solid dispersion is the dispersion of one or more active ingredients in hydrophilic inert carrier matrix at molecular level. Solid dispersions of poorly water-soluble drugs with water-soluble carriers have been reduced the incidence of these problems and enhanced dissolution. The focus of this review article is on advantages, disadvantages and the method of preparation, and characterization of the solid dispersion. This review also discusses the recent advances in the field of solid dispersion technology.